PENGARUH PRODUK, PELAYANAN, HARGA DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PIZZA HUT DI KOTA BENGKULU - Hermawati Hermawati; Syofian Syofian (Universitas Prof. Dr. Hazairin SH, 2021)
This research to determine how much influence the product, service, price and brand have on the decision to purchase pizza hut in Bengkulu city. The data analysis method used multiple linear regression. As many as 100 people as a sample determined by non-probability sampling technique with a purposive sampling approach.Data collection techniques used in this research are library research and field studies in the form of questionnaires, observations and interviews.Based on the results of the analysis in this study, it was found that the product, service, price, and brand variables had a significant effect on purchasing decisions by Pizza Hut consumers in Bengkulu City. In other words, the four independent variables together had a major influence on purchasing decisions.